Left atrial schwannoma in schwannomatosis: a case report - Kenji Yokoyama; Tomoya Yoshizaki; Dai Tasaki (Surgical Case Reports, 2021)
Abstract Background Primary cardiac schwannoma in the left atrium and schwannomatosis are rare diseases. Case presentation We report the case of a 46-year-old asymptomatic man who had tumor resection for parapharyngeal schwannoma at another institute 1 year ago. He was presented to our hospital for further evaluation of an abnormal cardiac shadow that was found incidentally. Computed tomography and transesophageal echocardiography revealed a cardiac tumor originating from the posterior wall of the left atrium, an atrial septal defect, and two other mediastinal tumors. The cardiac mass was completely excised with normal margins of the surrounding atrial wall. The post-resection defect and atrial septal defect were repaired using bovine pericardium. Pathological findings were compatible with benign schwannoma, and a diagnosis of schwannomatosis was made based on his medical history. Conclusion Primary cardiac schwannoma is an exceedingly rare tumor, and the incidence in schwannomatosis has not been reported in the literature.